Myths and truths in talent development - Collins, D.; MacNamara, A. (Talent development: A practitioner guide, 2018)
So much of the current TID scene is dominated by `pop-science` or half understood myths that it seems crucial to start with a severe questioning about the content and quality of sources for various high-profile ideas. To add to the challenge, sound ideas are often juxtaposed with some extremely questionable and unfounded concepts (e.g. critical windows in Long-Term Athlete Development, LTAD). In simple terms, this chapter aims to set out some clear criteria for readers to decide what is true and what is questionable. In a similar fashion, it offers some balance to later evidence by stressing that `how you should act depends on what you want`! As such, we offer evidence that contrasts early-age group accomplishment with senior success, exploring how, if at all and under what circumstances, these two apparent polar opposites may be combinable.